Thinking Styles Inventory: Psychometric features in college students from Buenos Aires - Freiberg, Agustín (2019)
Background: Thinking styles lead to describe how people use their abilities when they have to deal with problem solving situations. The Thinking Styles Inventory –TSI- is one of the most worldwide employed scales, developed to assess 13 thinking styles posed in the Theory of Mental Self-government -Legislative, Executive, Judicial, Monarchic, Hierarchic, Oligarchic, Anarchic, Global, Local, Internal, External, Liberal, Conservative. Method: Aiming at the adaptation of the scale to local college students’ population, linguistic aspects were reviewed as well as the response scale. After a pilot study, a sample composed of 361 college students from Buenos Aires responded the inventory in order to perform exploratory and confirmatory factorial analyzes on the one hand, and an internal consistency on the other. Result: A 7-factor structure -Judicial/Liberal, Executive/Conservative, External, Monarchic, Global, Hierarchic, Legislative-, was obtained. Conclusion: Such a version maintained 45 of the 104 tested items. Internal consistency of the extracted dimensions reached adequate values. Results are examined considering the theoretical model and further research lines.